ANALISIS KINERJA PERKALIAN MATRIKS PARALEL MENGGUNAKAN METRIK ISOEFISIENSI - Kartawidjaja, Maria A. (TESLA Jurnal Teknik Elektro UNTAR, 2008)
In solving a complex problem is often less adequate sequential computing, especially in terms of execution time is very long, and thus become not fisibel. An interesting alternative to overcome the long computational time is the use of parallel computing. Kompuasi parallel performance can be measured by various metrics, one of them is isoefisiensi. With predictable isoefisiensi scalability of a parallel system. As a test program used in this study and the vector matrix multiplication, the matrix is partitioned following the chessboard pattern. Test program is executed on a computer with hypercube architecture. From the test results can be concluded that the parallel system is scalable because it requires a small increase in weight along with the increase in the number of processors.